Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1002/bbpc.199500089
|View full text |Cite
|
Sign up to set email alerts
|

The Growth and Properties of Pd and Pt on Al2O3/NiAl(110)

Abstract: Small metal particles have strongly size-dependent properties, which -in the case of supported particles -are also influenced by the particle substrate interaction. We have investigated such effects for Pd deposited on a thin alumina film grown on NiAl(11 0) by probing the adsorption behaviour of CO. Structure and size of the metal islands were varied by employing different substrate temperatures during evaporation. We found that at 90 K small, disordered aggregates are formed, whereas deposition at 300 K resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
50
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 17 publications
(21 reference statements)
4
50
0
Order By: Relevance
“…Additionally, Heemeier et al have also shown that increasing the concentration of surface hydroxyl groups increases metal dispersion on metallic supported catalysts [17], presumably due to the addition of more nucleation sites for the initiation of metal particle growth. Recently, a number of research groups have developed the use of ultrathin films of Al 2 O 3 that can be grown on the surfaces of single crystals of the intermetallic compounds of Ni and Al as models for Al 2 O 3 catalyst supports [1,15,16,[18][19][20][21][22][23][24][25]. Such ultrathin films have a number of advantages for fundamental studies utilizing modern surface spectroscopies.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Heemeier et al have also shown that increasing the concentration of surface hydroxyl groups increases metal dispersion on metallic supported catalysts [17], presumably due to the addition of more nucleation sites for the initiation of metal particle growth. Recently, a number of research groups have developed the use of ultrathin films of Al 2 O 3 that can be grown on the surfaces of single crystals of the intermetallic compounds of Ni and Al as models for Al 2 O 3 catalyst supports [1,15,16,[18][19][20][21][22][23][24][25]. Such ultrathin films have a number of advantages for fundamental studies utilizing modern surface spectroscopies.…”
Section: Introductionmentioning
confidence: 99%
“…A knowledge of the morphology of supported metal nanoparticles is of tremendous importance in heterogeneous catalysis because the catalytic properties of nanoparticles strongly depend on their exact surface structure ( [1][2][3][4][5][6][7][8][9] and references therein). Metal nanoparticles often exhibit low Miller-index facets and single crystal surfaces have therefore frequently been used as model systems.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] The size of clusters and, hence, their geometrical and electronic structures can be controlled by changing formation conditions such as metal deposition rates and surface temperature. [6] Thus, it is of great interest to know if surface (photo)reactions can be controlled by manipulating the electronic and geometrical structures of the metal clusters.…”
mentioning
confidence: 99%